Crossing a CRISPR/Cas9 transgenic tomato plant with a wild-type plant yields diverse mutations in the F1 progeny - Ito, Yasuhiro (Frontiers in Plant Science, 2024)
Generating CRISPR/Cas9-mediated mutants in tomato (Solanum lycopersicum L.) involves screening shoots regenerated from cultured cells transformed with a T-DNA harboring sequences encoding Cas9 and single guide RNAs (sgRNAs). Production of transformants can be inconsistent and obtaining transformants in large numbers may be difficult, resulting in a limited variety of mutations. Here, I report a method for generating various types of mutations from one transgenic plant harboring the CRISPR/Cas9 system. In this method, a wild-type plant was crossed with a T0 biallelic mutant expressing two sgRNAs targeting the RIPENING INHIBITOR (RIN) gene, and the resulting F1 seedlings were classified using a kanamycin resistance marker on the T-DNA. Genotyping of the RIN locus revealed that kanamycin-sensitive F1 seedlings, which carried no T-DNA, always harbored the wild-type allele and a mutant allele from the transgenic parent. Kanamycin-resistant F1 seedlings, which do carry the T-DNA, harbored a variety of novel mutant alleles, but not the wild-type allele, suggesting that it was mutated during crossing. The novel mutations included onebase insertions or short deletions at each target site, or large deletions across the two target sites. This method was also successfully applied to produce mutations in Geranylgeranyl pyrophosphate synthase 2 (GGPS2). Because this method involves crossing rather than transformation, it can be readily scaled up to produce numerous novel mutations, even in plant species or cultivars for which transformation is inefficient. Therefore, when initial transgene experiments fail to induce the desired mutation, this method provides additional opportunities for generating mutants.